2020
DOI: 10.1177/0892705720904102
|View full text |Cite
|
Sign up to set email alerts
|

Treated basalt fibers reinforced nylon 6,6/epoxy hybrid nanofibril composites

Abstract: Basalt fiber was first treated in a mixture of formic acid (FA) and dichloromethane (DCM) to reduce its diameter down to one micrometer. Electrospinning process was utilized to produce treated basalt fiber (TBF)-reinforced nylon 6,6/epoxy (NY/EP) hybrid nanofibril composites. NY/EP polymers have been dissolved in 80:20 mixture of FA/DCM solvent to form a homogenous solution. TBFs with different weight ratios of 5, 10, 15, 20, and 25 wt% were added to NY/EP (ratio of 5:1). The morphology of the hybrid nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Only 9wt.% EGNS, on the other hand, demonstrated a decrease in Tg due to its substantial free volume (void) resulting from excess EGNS aggregates and cause the segmental motions in the polymer network to increase. 53,54
Figure 6.DSC thermogram of PS loaded with EGNS Composite nanofiber mats.
…”
Section: Resultsmentioning
confidence: 99%
“…Only 9wt.% EGNS, on the other hand, demonstrated a decrease in Tg due to its substantial free volume (void) resulting from excess EGNS aggregates and cause the segmental motions in the polymer network to increase. 53,54
Figure 6.DSC thermogram of PS loaded with EGNS Composite nanofiber mats.
…”
Section: Resultsmentioning
confidence: 99%
“…The main goal of this research is to develop controllable aspects in order to improve mechanical strength qualities. At three stages, the type of reinforcing materials, the weight percent of support content, and the injection moulding pressure are all monitored [15]. In light of the writing overview, the reaches for the cycle boundaries are set.…”
Section: Reinforcement Materials-sic and B 4 Cmentioning
confidence: 99%
“…Experimentation has been carried out in this regard to assess the temperature that occurs in the gear box of a moped when nylon 66 helical gear is used instead of metal gear [1]. Through the analysis in polymer composite gear with reinforcement of E-Glass GSM in various proportions, detailed analysis concluded that polymer composite gears have less wear rate related with conventional cast iron gears [15]. Composite was made using nylon 66 with various percentages of silica fume particulates through injection moulding machine to examine tensile, compression, flexural, impact, and heat distortion temperature (HDT).…”
Section: Introductionmentioning
confidence: 99%
“…Various fibers were also used to improve the mechanical and tribological properties of polymers for decades. In one recent research, formic acid and dichloromethanetreated basalt fibers enhanced the tensile strength, young's modulus, and thermal stability of nylon 66/epoxy composites (21). In another recent research, 13 wt% bamboo mesoparticles enhanced the tensile strength, modulus, and flexural strength of nylon 6 by a few percentages (22).…”
Section: Introductionmentioning
confidence: 96%